Gaucher's disease in the United Kingdom: screening non-Jewish patients for the two common mutations. Issue 4 (April 1993) - Walley, A J; Barth, M L; Ellis, I; Fensom, A H; Harris, A
Abstract : Twenty-six patients with Gaucher's disease diagnosed in the United Kingdom and two obligate carriers, all of non-Jewish origin, were screened for the two common disease causing mutations and two rarer mutations in the glucocerebrosidase gene. These mutations are referred to as N370S, L444P, Ins84G, and 1066 + 1G-->A, respectively. The results showed that out of 54 alleles screened, 26% were N370S, 35% were L444P, and the remaining 39% were rare or undefined. The results also showed a clear correlation between the presence of at least one N370S allele and mild disease.